Community-Based Mental Health Promotion: “Gerakan Sehati (Sehat Jiwa dan Hati)” as a Preventive Effort Against Mental Disorders in Pogung Village, Klaten - Yonanda, Innes (IAI Nasional Laa Roiba Bogor, 2025)
Mental health disorders remain an under-addressed health issue, especially in rural areas with limited access to information and mental health services. This study aimed to improve mental health literacy through the community-based intervention program “Gerakan Sehati (Healthy Mind and Heart Movement)” in Pogung Village, Cawas District, Klaten Regency, Central Java. The method used was a participatory approach consisting of assessment, intervention, and evaluation phases. Data were collected through observation, interviews, focus group discussions (FGDs), and document studies. The results showed that prior to the intervention, the community had low awareness regarding mental health disorders and their treatment. Following the intervention, which included psychoeducation, health counseling, relaxation techniques, and the formation of community health cadres, there was a significant increase in knowledge as indicated by pre-test and post-test scores (Z = -3.675, p < 0.05). The program also successfully established village cadres capable of early detection and referral. These findings indicate that multi-stakeholder community programs are effective in enhancing awareness and concern for mental health.